Production of Coffee Cherry Spirits from Coffea arabica Varieties - Patrik Blumenthal; Marc C. Steger; Andrès Quintanilla Bellucci; Valerie Segatz; Jörg Rieke-Zapp; Katharina Sommerfeld; Steffen Schwarz; Daniel Einfalt; Dirk W. Lachenmeier (Foods, 2022)
Coffee pulp, obtained from wet coffee processing, is the major by-product accumulating in the coffee producing countries. One of the many approaches valorising this underestimated agricultural residue is the production of distillates. This research project deals with the production of spirits from coffee pulp using three different Coffea arabica varieties as a substrate. Coffee pulp was fermented for 72 h with a selected yeast strain (Saccharomyces cerevisiae L.), acid, pectin lyase, and water. Several parameters, such as temperature, pH, sugar concentration and alcoholic strength were measured to monitor the fermentation process. Subsequently, the alcoholic mashes were double distilled with stainless steel pot stills and a sensory evaluation of the products was conducted. Furthermore, the chemical composition of fermented mashes and produced distillates were evaluated. It showed that elevated methanol concentrations (>1.3 g/L) were present in mashes and products of all three varieties. The sensory evaluation found the major aroma descriptor for the coffee pulp spirits as being stone fruit. The fermentation and distillation experiments revealed that coffee pulp can be successfully used as a raw material for the production of fruit spirits. However, the spirit quality and its flavour characteristics can be improved with optimised process parameters and distillation equipment.